Energy saving laser weeding: Heat transfer simulation to reveal ablation mechanism and predict energy consumption - Wantong Zhang; Haochen Zhu; Jiyu Sun (Computers and Electronics in Agriculture, 2026)

Eco-friendly fluidized solidified loess incorporating multi-source industrial solid wastes: A systematic study from rheological features, mechanical performance, and stabilization mechanisms - Baofeng Lei; Jucong Sun; Henghui Fan; Yongxiang Cao; Changhao Liu; Haochen Zhang; Shuai Pang; Jiaze Li; Huihui Yu; Minqiang Meng (Process Safety and Environmental Protection, 2026)

Occurrence, seasonal variability, and ecological risk of emerging contaminants in estuarine and nearshore waters around Hainan Island, China - Haochen Niu; Yuehua Huang; Sichen Li; Xueqing Zhou; Chuhan Sun; Hongwei Zhao (Marine Environmental Research, 2026)

Ultrasound-activated azido-sulfonamide prodrug nanoparticle with antibacterial peptide targeting for selective bacterial infection therapy - Jiali Sun; Jiahui Pan; Xitong Ren; Zecheng Chang; Wenfang Wang; Guoqing Wang; Jianting Xu; Jianshi Du; Haochen Yao (Chemical Engineering Journal, 2026)

Dairy flavor measurements from materials to human perception: Emerging trends and applications - Yangfan Guo; Ying Wang; Haochen Zhou; Xinying Xu; Dongxiao Sun-Waterhouse; Shan Ding; Fanyu Meng; Tao Jiang; Bei Wang (Trends in Food Science & Technology, 2026)

Patterns and causes of ammonia nitrogen enrichment in groundwater of a typical agricultural irrigation area in the northern Henan Plain, China - Haoyang Li; Liang Zhang; Mingming Luo; Xiaoyang Liu; Gaoxin Xiao; Ruihua Shang; Shuna Sun; Haochen Gu; Chengyi Zu (Environmental Geochemistry and Health, 2026)

Multimodal bioinspired flapping-wing vehicle (M−bioFMAV): Design and aerodynamic optimization for agricultural plant protection in greenhouses - Haochen Zhu; Wantong Zhang; Jiyu Sun (Computers and Electronics in Agriculture, 2026)

Mobile MAX-DOAS measurements and source analysis of NO2, HCHO, and HONO during the Chengdu 2023 FISU world university games - Qijin Zhang; Chengzhi Xing; Miao Feng; Yinshuo Ding; Zhongmou Sun; Yikai Li; Haochen Peng; Wei Tan; Zhiguo Zhang; Tianjun Du; Cheng Liu (Journal of Environmental Sciences, 2026)

A comparative study on the occurrence and pore structure characteristics of CH4 and CO2 hydrates in sandy sediments using SEM-EDS technology - Lujun Wang; Haochen Yang; Chuanqi Sun; Jianye Sun; Xiluo Hao; Chengfeng Li; Bin Zhu; Yunmin Chen (Gas Science and Engineering, 2026)

Impact of biochar on the fate of 15N-labelled fertilizer in water-saving and flooding irrigated rice-soil system under three different nitrogen sources - Xi Chen; Zhihui Wang; Ningbo Cui; Li Guo; Kangning Yu; Haochen Jin; Shikuan Sun (Plant and Soil, 2025)

Integrating AI into OLED material design: a comprehensive review of computational frameworks, challenges, and opportunities - Yiming Shi; Ming Sun; Haochen Shi; Zhiqin Liang; Bo Qiao; Suling Zhao; Xuemei Pu; Dandan Song (Science Bulletin, 2025)

Cigarette smoke-induced PPAR signaling dysregulation accelerates Alzheimer's disease pathogenesis and cognitive decline in 5xFAD mice - Yunqi Xie; Haochen Wang; Yajie Zhang; Bingbing Lin; Yuting Chen; Kai Li; Huanwen Tang; Qian Sun (Food and Chemical Toxicology, 2025)

Delineating and refining the equity of revealed accessibility of express service amenities: A case study of Guangzhou - Yankai Wang; Quanyu Liu; Tao Mei; Haochen Shi; Miaoxi Zhao; Binbin Sun (Applied Geography, 2025)

Thermokinetic analysis of surface-active groups in coal using ultrasonic extraction method - Yaqing Li; Xinxin Sun; Yutao Zhang; Jun Deng; Kexin Liu; Yuanbo Zhang; Qiang Guo; Haochen Li (Fuel, 2025)

Bioinspired tailless FWMAV design for agricultural plant protection in greenhouses - Yongwei Yan; Fa Song; Wenzhe Wang; Haochen Zhu; Jiyu Sun (Computers and Electronics in Agriculture, 2025)

Numerical simulation of cavity evolution and motion characteristics of double hollow cylinders in oblique water entry - Hao Yuan; Xidong Zhou; Haochen Ling; Qian Sun; Chun Yang (Ocean Engineering, 2025)

The outer-inner loop mechanism of alkali carbonate-modified BaFe2O4 during the biomass char chemical looping partial oxidation and hydrogen generation (CLPH) process - Haochen Sun; Hengyang Miao; Zhiqing Wang; Zheyu Liu; Chao He; Yitian Fang (Chemical Engineering Journal, 2025)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Copper-doped orange peel biochar activated peroxydisulfate for efficient degrading tetracycline: The critical role of C-OH and Cu - Haochen Li; Haochao Sun; Qiang Li; Xiaofei Zong; Longli Wu; Zhengyu Han; Xinyu Li; Jiahui Wu; Yuxuan Ye; Fei Pan (Environmental Research, 2024)

Relying on free radical degradation of cephalexin by novel Cu1Co2@C catalyzed by permonosulfate: Mechanism and degradation pathways - Xiaofei Zong; Xinyu Li; Jiahui Wu; Xi Ni; Haochen Li; Zhengyu Han; Rongling Wang; Yuwei Deng; Yuxuan Ye; Lei Sun; Qiang Li; Fei Pan (Journal of Water Process Engineering, 2024)

Three-stage behaviors of K2CO3 catalyst during CO2 catalytic gasification of coal - Haochen Sun; Zhiqing Wang; Hengyang Miao; Yangang Mei; Jiejie Huang; Jin Bai; Yitian Fang (Fuel, 2024)

Global Environmental Change Shifts Ecological Stoichiometry Coupling Between Plant and Soil in Early-Stage Invasions - Guangqian Ren; Miaomiao Cui; Haochen Yu; Xue Fan; Zhaoqi Zhu; Haiyan Zhang; Zhicong Dai; Jianfan Sun; Bin Yang; Daolin Du (Journal of Soil Science and Plant Nutrition, 2024)

Highly efficient adsorption of ciprofloxacin from aqueous solutions by waste cation exchange resin-based activated carbons: Performance, mechanism, and theoretical calculation - Qiang Li; Haochen Li; Xiaofei Zong; Haochao Sun; Yunhao Liu; Ziyi Zhan; Shou Mei; Yanjie Qi; Yangbo Huang; Yuxuan Ye; Fei Pan (Science of The Total Environment, 2024)

Spatial patterns of zooplankton abundance, biovolume, and size structure in response to environmental variables: a case study in the Yellow Sea and East China Sea - Song Sun; Haochen Xian; Xiaoxia Sun; Mingliang Zhu; Mengtan Liu (Journal of Oceanology and Limnology, 2024)

Recognizing iso-olefins as paramount intermediates for optimum isoparaffins production via CO hydrogenation - Haochen Qi; Cederick Cyril Amoo; Wuqiang Si; Jian Lou; Xuangan Liu; Chunyang Zeng; Qingjie Ge; Jian Sun; Chuang Xing; Xinhua Gao (Fuel, 2023)

Efficient HCl leaching of platinum group metals from waste three-way catalysts: A study on kinetics and mechanisms - Shiqiang Sun; Wenting Zhao; Chenxi Jin; Wenzhi He; Guangming Li; Haochen Zhu (Environmental Research, 2023)

Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2023)

A lightweight deep learning model for ocean eddy detection - Haochen Sun; Hongping Li; Ming Xu; Fan Yang; Qiang Zhao; Cuishu Li (Frontiers in Marine Science, 2023)
Ocean eddies are typical oceanic mesoscale phenomena that are numerous, widely distributed and have high energy. Traditional eddy detection methods are mainly based on physical mechanisms with high accuracy. However, the large number of steps and complex parameter settings limit their applicability for most users. With the rapid development of deep learning techniques, object detection models have been broadly used in the field of ocean remote sensing. This paper proposes a lightweight eddy detection model, ghost eddy detection YOLO (GED-YOLO), based on sea level anomaly data and the “You Only Look Once” (YOLO) series models. The proposed model used ECA+GhostNet as the backbone network and an atrous spatial pyramid pooling network as the feature enhancement network. The ghost eddy detection path aggregation network was proposed for feature fusion, which reduced the number of model parameters and improved the detection performance. The experimental results showed that GED-YOLO achieved better detection precision and smaller parameter size. Its mAP was 95.11% and the parameter size was 22.56 MB. In addition, the test experiment results showed that GED-YOLO had similar eddy detection performance and faster detection speed compared to the traditional physical method.

The fate of microplastic pollution in the Changjiang River estuary: A review - Yifei Li; Qingbing Lu; Jian Yang; Yi Xing; Wei Ling; Kai Liu; Qizhen Yang; Hongjie Ma; Zengxin Pei; Tianqi Wu; Haochen Guo; Ziyuan Gao; et al. (Journal of Cleaner Production, 2023)

Physical processes determining the distribution patterns of Nemopilema nomurai in the East China Sea - Song Sun; Haochen Xian; Ziyuan Hu; Xiaoxia Sun; Fang Zhang (Journal of Oceanology and Limnology, 2023)

Failure analysis of three-way catalysts through comprehensive characterization and understanding the role of pretreatment - Shiqiang Sun; Chenxi Jin; Wenzhi He; Guangming Li; Haochen Zhu; Juwen Huang (Journal of Environmental Chemical Engineering, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Comparative life cycle assessment of whiteleg shrimp (Penaeus vannamei) cultured in recirculating aquaculture systems (RAS), biofloc technology (BFT) and higher-place ponds (HPP) farming systems in China - Yue Sun; Haochen Hou; Dengpan Dong; Jiasong Zhang; Xiaohan Yang; Xian Li; Xiefa Song (Aquaculture, 2023)

Process and mechanism of enhanced HCl leaching of platinum group metals from waste three-way catalysts by Li2CO3 calcination pretreatment - Shiqiang Sun; Chenxi Jin; Wenting Zhao; Wenzhi He; Guangming Li; Haochen Zhu; Juwen Huang (Journal of Hazardous Materials, 2023)

Comparative genomics revealed that Vibrio furnissii and Vibrio fluvialis have mutations in genes related to T6SS1 and T6SS2 - Jiakai Sun; Haochen Su; Wenhui Zhang; Xuesong Luo; Ruichao Li; Ming Liu (Archives of Microbiology, 2023)

Cleaner Production assessment for sea cucumber aquaculture: methodology and case studies in Dalian, China - Haochen Hou; Shuai Shao; Yun Zhang; Delin Sun; Qiuying Yang; Chenglu Qin; Xiaoyang Sun (Clean Technologies and Environmental Policy, 2019)

Improved design for textile production process based on life cycle assessment - Yun Zhang; Hong Kang; Haochen Hou; Shuai Shao; Xiaoyang Sun; Chenglu Qin; Shushen Zhang (Clean Technologies and Environmental Policy, 2018)

Controlling mechanism of absence seizures by deep brain stimulus applied on subthalamic nucleus - Bing Hu; Yu Guo; Xiaoqiang Zou; Jing Dong; Long Pan; Min Yu; Zhejia Yang; Chaowei Zhou; Zhang Cheng; Wanyue Tang; Haochen Sun (Cognitive Neurodynamics, 2018)